Breast cancer: relation between quality of life and physical activity level - Marina Ribovski; Adriana Coutinho de Azevedo Guimarães; Leonessa Boing; Fabiana Flores Sperandio; Mirella Dias; Nycolle Martins Reis (Revista Brasileira de Atividade Física e Saúde)
The objective was to investigate the relation between quality of life and physical activity level in women with breast cancer undergoing treatment at the Oncologic Research Center (CEPON). A total of 158 women (56±9 years) answered a structured questionnaire, at a standardized interview, about sociodemographic and clinical information; economic situation (IBGE – Instituto Brasileiro de Geografia e Estatística); physical activity (IPAQ – International Physical Activity Questionnaire); and quality of life (QLQ-C30 – Quality of Life Questionnaire; QLQ-BR23). Most of the women was not sufficiently active (71.5%) and reported better global quality of life, with a score of 73±25. There was a significant difference on the functional scale for the items physical function (p=0.007) and role performance (p=0.048), with better quality of life values for active women, as well as on the symptom scale for the items loss of appetite (p=0.005) and pain (p=0.040). There was a positive association between total physical activity and quality of life in physical function (r=0.23; p=0.01) and role performance (r=0.023; p=0.01) and a negative association in the symptom scale (r=-0.24; p=0.01) and item loss of appetite (r=- 0.25; p=0.01). We conclude that women with breast cancer were not sufficiently active and showed good global quality of life scores, being that the actives presented better physical function, role performance and less loss of appetite and pain.